2016
DOI: 10.1111/acem.13063
|View full text |Cite
|
Sign up to set email alerts
|

Funding Research in Emergency Department Shared Decision Making: A Summary of the 2016 Academic Emergency Medicine Consensus Conference Panel Discussion

Abstract: T he 2016 Academic Emergency Medicine (AEM) Consensus Conference was focused on creating a policy-relevant, patient-centered research agenda for shared decision making (SDM) in the emergency department (ED). As part of the conference, representatives of a diverse group of funding agencies were assembled to serve on a panel addressing strategies and opportunities to secure funding in ED SDM research. The panel met as a group three times in the year leading up to the conference to identify examples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…On a societal level, SDM has been shown to reduce unnecessary care and decrease the possibility of harm; it may also reduce healthcare costs . Although this collaborative process has been widely discussed and documented in a broad spectrum of medical and surgical specialties, research assessing its use in otolaryngology is scant and has been identified as a gap in knowledge …”
Section: Introductionmentioning
confidence: 99%
“…On a societal level, SDM has been shown to reduce unnecessary care and decrease the possibility of harm; it may also reduce healthcare costs . Although this collaborative process has been widely discussed and documented in a broad spectrum of medical and surgical specialties, research assessing its use in otolaryngology is scant and has been identified as a gap in knowledge …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, SDM has been shown to reduce unnecessary care, decrease the possibility of harm, and may also reduce healthcare costs . Although this collaborative process has been widely discussed and documented in a broad spectrum of medical and surgical specialties, research assessing its use in otolaryngology is scant and has been identified as a gap in knowledge …”
Section: Introductionmentioning
confidence: 99%
“…6 Additionally, SDM has been shown to reduce unnecessary care, decrease the possibility of harm, and may also reduce healthcare costs. 7 Although this collaborative process has been widely discussed and documented in a broad spectrum of medical and surgical specialties, 3,[8][9][10][11][12][13] research assessing its use in otolaryngology is scant and has been identified as a gap in knowledge. 2,14,15 One of the ways in which SDM is implemented into clinical practice is through the use of shared decisionmaking tools (SDMTs) to evaluate possible treatment options on individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…The funding panel included Marcus Escobedo, MPA from the John A. Hartford Foundation, Jeremy Brown, MD from the NIH Office of Emergency Care Research, Brendan Carr, MD from the U.S. Department of Health and Human Services, Patrick Dunn, PhD from the American Heart Association, and Christopher Gayer, PhD from the Patient Centered Outcomes Research Institute. 21 …”
Section: Conference Agenda (Figure 1)mentioning
confidence: 99%